EMPIRICAL STUDY OF INCOME MANAGEMENT BASED ON CASH FLOWS, AUDITOR QUALITY AND COMPANY VALUE IN INDONESIA - Marheni Marheni (Fakultas Ekonomi, Universitas Bangka Belitung, 2021)
AbstractThis study aims were to determine the effect of cash flow-based earnings management on firm value as moderated by the variable Good Corporate Governance. This research is explanatory research. The research population is manufacturing companies on the Indonesia Stock Exchange in 2014-2015. Methods of data analysis using Moderating Regression Analysis (MRA). This study explains that cash flow-based earnings management has an effect on firm value. Auditor quality has a significant effect on firm value. Likewise, management ownership has no effect on firm value. Keywords: earnings management, cash flow, company value and Good Corporate Governance